Manejo de plásticos empleado en la producción bananera en el cantón el Guabo Provincia de El Oro - Romero Erreyes, Richard Alexander (2017)
Ecuador is one of the main producers of bananas and the one that has the best fruit worldwide due to good phytosanitary and labor practices. But a serious problem that exists in most of the farms or farms of the country is the pollution that exists with the waste of plastics, that are used in the banana plantations because these products cause a great environmental impact, for the people due to this There are many people affected in the canton El Guabo. If we talk about banana protection during harvesting we have to involve the use of foam protectors, which are placed between the hands of clusters to avoid damage of clusters, when Are transferred, also used a lot what are the covers with treatments which protect from insects to fruits, the vast majority of the fruit are exported to other countries and are not left in the domestic market, because we only consume the inhabitants The rejection of the banana plantations. The plastic elements that are used in agricultural farms after their function become polluting garbage, because they did not have a recycling process, the majority of these products are of slow decomposition, generating high amounts of residues that remain in sight Of people living close to farms causing agricultural, environmental pollution, and visual pollution and sometimes it seems that these places were abandoned because of the large accumulation of garbage. The present work shows an analysis of the main uses of these products and the degradation it has and its possible environmental cost, guided by recommendations for their respective and adequate management, to be able to take the respective decisions and to carry out a control measure that allows them Banana companies control the misuse of waste, carry out campaigns, and give suggestions to the Ministry of Agriculture to ensure greater control in the farms and farms of the country and the people of the canton El Guabo. The need to decrease The accumulation of plastic waste is driving alternative systems to their recycling and accumulation in containers. The use of plastics in banana plantations is a growing need worldwide, due to its wide variety of applications in the agricultural process, where daily new possibilities of use are found and as a solution to various daily life needs in society; However, at the same time, once it is used, it becomes a non-degradable waste and a significant environmental problem, if no pathways are sought for its recycling, that is to say, to turn them into usable products of the same characteristic or converted into other useful products . Once plastic is used it becomes a significant environmental problem, if no pathways are sought for its recycling, that is, turn them into profitable products of the same characteristics or converted into other useful products. The surveys allowed to obtain data of each one of the variables that was presented and allowed to obtain information of the banana farms of the sector that at the present time are not handled of suitable form. It was concluded that the real possibilities of lowering the contamination would be through the application Of campaigns, norms and laws that regulate the negative impacts that produce the banana sector and try to raise the awareness of producers to take the necessary measures.